KOMPOSISI HASIL TANGKAPAN RARAPE (BOTTOM GILLNET) DI DESA KULU KECAMATAN LIPKUPANG, KABUPATEN MINAHASA UTARA - Heru Santoso; Jul Manohas; Mohammad Zaini; Yuli Purwanto; Johnny H. Tumiwa; Jerry D. Kalesaran (JURNAL BLUEFIN FISHERIES, 2022)
The aim of this research was to determine the species composition (Kj) and the weight composition (Kb) of the catch using a bottom gillnet whom operated by fishermen the village of Kulu. The research was conducted from October to December 2020. The research method was experimental fishing using gillnets with a 3 inch mesh size. The fishing operation took place over 15 trips and the fishing area was around the waters of the village of Kulu. The results showed that the catch was 117 fish including 15 kinds of fish and one type crustacean. The composition based on the dominant fish species is Naso hexacanthus (29.06%), whereas the composition based on the dominant weight is Portunus pelagicus (33.6%). Keywords : bottom gillnet, composition, kulu village